mHealth and telemedicine apps: in search of a common regulation - Crico, Chiara; Renzi, Chiara; Graf, Norbert; Buyx, Alena; Kondylakis, Haridimos; Koumakis, Lefteris; Pravettoni, Gabriella (Ecancermedicalscience, 2018)
Developments in information and communication technology have changed the way healthcare processes are experienced by both patients and healthcare professionals: more and more services are now available through computers and mobile devices. Smartphones are becoming useful tools for managing one’s health, and today, there are many available apps meant to increase self-management, empowerment and quality of life. However, there are concerns about the implications of using mHealth and apps: data protection issues, concerns about sharing information online, and the patients’ capacity for discerning effective and valid apps from useless ones. The new General Data Protection Regulation has been introduced in order to give uniformity to data protection regulations among European countries but shared guidelines for mHealth are yet to develop. A unified perspective across Europe would increase the control over mHealth exploitation, making it possible to think of mHealth as effective and standard tools for future medical practice.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Data protection; European community; Mobile apps; Patient data privacy; Telemedicine